The Arguments to Social Apathy in Song of Losing My Religion by R.E.M - Muhammad Adji Mullah Akbar; Salsabila Nova Calista; Rommel Utungga Pasopati; Kusuma Wijaya (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2023)
Apathy is lack of interest or paying no attention to any social circumstance around. The idea is also indicated in various literary works including songs. Losing My Religion is a literary work created by the band R.E.M in the form of a song that talks about the heart of someone who lost his faith. The person has done many things for the people he loved but got no reply at all. He lost faith in what he wanted to pursue since he would never get no matter how many he tried. Then, how may social apathy be correlated with Losing My Religion by R.E.M? Through qualitative method, this paper underscores failure felt by the person in the song shapes social apathy towards his or her position in society. Gradually, the apathy affected the person’s mentality to never trust anyone anymore. He will only believe any reality as dream. In conclusion, the lack of social sense and a strong sense of apathy will greatly damage people's mentality as reflected on the song. The person only looks down upon the person he or she loves, but the other denied the love by showing apathetic personality.